Morphology and Biochemistry of Ovulation Morfologia e bioquímica da ovulação - Sebastião Freitas de Medeiros; Bruna Barcelo Barbosa; Matheus Antonio Souto de Medeiros; Márcia Marly Winck Yamamoto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract The process of ovulation involves multiple and iterrelated genetic, biochemical, and morphological events: cessation of the proliferation of granulosa cells, resumption of oocyte meiosis, expansion of cumulus cell-oocyte complexes, digestion of the follicle wall, and extrusion of the metaphase-II oocyte. The present narrative review examines these interrelated steps in detail. The combined or isolated roles of the folliclestimulating hormone (FSH) and luteinizing hormone (LH) are highlighted. Genes indiced by the FSH genes are relevant in the cumulus expansion, and LH-induced genes are critical for the resumption ofmeiosis and digestion of the follicle wall. A nonhuman model for follicle-wall digestion and oocyte release was provided.